B Lymphocyte—A Prognostic Indicator in Post‐Acute Pancreatitis Diabetes Mellitus - Xiaoyan Lin; Xiaoling Li; Junsheng Wang; Huiheng Liu (Journal of Diabetes)
ABSTRACT Objective To determine the value of lymphocyte subsets and granulocyte/monocyte surface markers in predicting the risk of post‐acute pancreatitis diabetes (PPDM‐A). Methods This study included 308 in patients with acute pancreatitis (AP). The markers of granulocytes and monocytes and lymphocyte subsets were detected by flow cytometry, and the fluorescence intensity, absolute count and percentage were obtained. Based on the occurrence of diabetes after AP, patients were divided into two groups: PPDM‐A and PPNG‐A (post‐acute pancreatitis with normal glucose). Correlations between granulocyte and monocyte surface markers and lymphocyte subsets were analyzed. Binary logistic regression was used to analyze the potential influencing factors of PPDM‐A. Results Compared with patients with PPNG‐A, patients with PPDM‐A tend to be younger (p < 0.001) and have a higher proportion of fatty liver, recurrent pancreatitis, and hyperlipidemic pancreatitis. The results of linear regression showed that B% was negatively correlated with MFI of HLA‐DR on monocytes (R2 = 0.145, p < 0.001), B% was positively correlated with CD10−NEUT% (R2 = 0.291, p < 0.001), and MFI of HLA‐DR on monocytes was negatively correlated with CD10−NEUT% (R2 = 0.457, p < 0.001). Multivariate logistic regression analysis revealed that age, serous effusion, fatty liver, recurrent pancreatitis, and B% were independent risk factors for the occurrence of PPDM‐A. Conclusion Our study has first confirmed the correlation between PPDM‐A and lymphocyte subsets and CD10−NEUT%. Furthermore we indicated that age, fatty liver, serous effusion, recurrent AP, and B% were independent risk factors for PPDM‐A. The mechanism of granulocyte and monocyte surface markers and B lymphocytes on PPDM‐A is worthy of study. This would help clarify the pathogenesis of PPDM‐A at the cellular level and potentially provide new strategies for immunotherapy and even disease prevention. [Correction added on 24 January 2025, after first online publication: the third subtitle in Abstract section has been changed to ‘Results’.]